أبعاد الكتابة الفاعلة في الخطاب المسرحي لأديب أحمد رضا حوحو - مومن موسى، كنزة, قليدة، خنساء (University of El-oued, 2022)
إن تسميه المسرح بأبي الفنون، ليس أمرا اعتباطيا ذلك أن هذا الفن منفتح على النفس البشرية ومكنوناتها يخاطبها ويواسيها ويعلمها ويوعيها في حلة فنية وأسلوب عذب قريب من الأرواح وهو فن قديم قدم البشرية وصولا إلى العصر الحديث والمعاصر وقد عرف تطورات ومؤثرات عديدة شأنه في ذلك شأن الجوانب الحياتية الأخرى، ولعلنا نلتفت إلى المسرح الجزائري وتطوره من نشاطات وعروض بسيطة لم تلق في البداية تجاوبا وسط المجتمع الجزائري إلى مسرحيات كاملة لها مضامينها وأهدافها .وبما أن المسرح هو أحد الأشكال الأدبية السردية فقد عملنا في هذا البحث على دراسة بنيته من شخصيات وزمان ومكان إضافة إلى العنوان وبعض الآليات غير اللغوية وجمالية توظيفها وذلك من خلال مسرحيات الأستاذ، بائعة الورد، ملكة غرناطة للأديب أحمد رضا حوحو رائد المسرح الجزائري والذي كرس جل أعماله لخدمة المجتمع فتعددت قضايا مسرحياته منها التربية والتعليم والمرأة والتاريخ وقد خلصنا إلى إبداع حوحو في تطويع البنية السردية لصالح البنية الاجتماعية بالوقوف على أبعاد العناوين والشخصيات والزمكان ودلالات كل ذلك في المسرحيات المختارة، مما انتج مسرحيات هادفة التزم فيها الكاتب بقضايا وطنه ومجتمعه مع إتقانه للتخفي وراء أقنعة فنية غرضها تقديم نقد أو اعتراض على الأوضاع المتردية في المجتمع أملا في إيجاد آذان صاغية وعقول واعية تعمل على الإصلاح. The theater was known as the father of arts. This fact is not arbitrary، king that this art is open to the human soul، it addresses her، comforts her، teaches her and sensitizes her in a rich suit and sweet style that is close to soul. It is a fan din who introduced humanity down to the modern and contemporary era، it has known many developments and influences that affect other aspects of life، perhaps we turn to the Algerian the theater and its development from simple activities and performances، that initially did not receive a response among Algerian society، to complete plays with their contents and goals. Sins theater is one of the literary narrative forms، where worked in this research to study its structure and components of personalities، time and place in additinante the title and son non linguistic me charismas and the aesthetics of its employment through plays by the professor، the flower seller، the queen of Granada by the writer Ahmed Reda Houhou the pioneer of the Algerian theater، who devoted most of his works to the service of society، and his plays were many issues، including education، woman and history we have concluded the creativity of Reda Houhou in adapting the narrative structure to serve the social structure by identifying the dimensions of titles، characters، time and place their connotations in the selected plays، which produced purposeful plays in wich committed to the issues of his country and society، with his mastery of hiding behind rich masks whose purpose is to present criticism or hypothesis on the deteriorating conditions in society in the hope of finding attentive ears and conscious minds working on reform.
Keywords: الكتابة، الخطاب،